Globalization in the 21st Century and Its Effects on Entrepreneurism and Innovation Ecosystems: A Call to Action for Africa - Wood, Van R.; Price, Brandon J.; Martens, Hans (Archives of Business Research, 2023)
In this paper, we briefly discuss how globalization has, over the last thirty years, influenced virtually every aspect of world political, economic, social and environmental development. This discussion will set the stage for our overview of innovation and entrepreneurism and economic development, gleaning insight from a report from Ernst & Young (see The Power of Three 2013) and from another report focusing data from 49 African countries (see - “Global Entrepreneurship Monitor – 2018/2019 Annual Report”). This is then followed by insights representing a “European perspective” on developing entrepreneurship in Africa. Finally, we focus on what needs to be done to further grow entrepreneurism and innovation in Africa and then provide a “call to action” to achieve this growth.